The evolution and development of railway passenger transportation clearing method in China - Yin Zhou; Wei Fang; Yan Xu; Huaixiang Wang; Lu Liu (Railway Sciences)
Purpose – As an important part of the management of railway passenger transport, the rationality and effectiveness of the clearing method of railway passenger transport are directly related to the operating efficiency and service quality of railway passenger transport enterprises. This paper aims to comprehensively and deeply discuss the evolution and development process of China’s railway passenger transport clearing method, analyze its characteristics and influences in each stage, identify the main factors affecting its evolution and development and then put forward thoughts on improving the future development of the clearing method. Design/methodology/approach – Through a detailed review of the railway passenger transport clearing methods from the planned economy period to the reform and opening up period and into the new century, the basis, mode, subject and object of clearing in different development stages are systematically compared. Findings – It comprehensively reveals the evolution of the clearing method, sorted out the characteristics and changes of the clearing method at each stage and the adaptability to the development of railway passenger transport at that time. The characteristics of the development of clearing measures for railway passenger transport in different stages and their far-reaching influence on railway passenger transport business are deeply analyzed. Originality/value – This paper summarized the factors influencing the development of China’s railway passenger transportation clearing approach evolution, including the simplified rules of clearing, enhanced the market adaptability, establishing and perfecting the incentive mechanism, strengthening the construction of informatization, etc. This paper puts forward the ways to improve the railway passenger transportation clearing future development thinking.